A battery housing, a battery including the housing, and an electric device thereof
By controlling the relationship between the content of Ti and Nb, the shell height and end wall thickness, the problem of steel being prone to break during deep drawing processing is solved, efficient deep drawing and good mechanical properties of the battery case are achieved, and the safety and processing yield of the battery are improved.
Patent Information
- Application Number
- CN202411556207.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-11-04
AI Technical Summary
In the prior art, steel is used as the material for the battery case for deep-tending processing, fracture is prone to occur.
By controlling the relationship between the content of Ti and Nb, the shell height and end wall thickness, the deep tensile properties of the steel are ensured, and the stress concentration caused by fracture during deep tensile forming is avoided. Specifically, the components of the steel include Ti, Nb and Cr, wherein the mass percentage of Cr is ≥16 wt.%, and the mass percentage of Ti and Nb is between 0.05-0.2 wt.% and 0.17-0.5 wt.%.
The battery case is efficient in deep drawing processing and good mechanical properties after forming, avoiding fracture, and improving processing yield and battery safety.
Smart Images

Figure CN119069898B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a battery casing, a battery comprising the casing, and an electrical device thereof. Background Art
[0002] With the increasing popularity of new energy vehicles, power batteries, as the core components of new energy vehicles, directly determine the vehicle's range, performance and overall safety. Among them, the battery shell, as an important component of the power battery, is related to the safety, energy density, service life and other battery performance of the power battery. Therefore, the battery shell is required to be lightweight and have relatively excellent mechanical properties.
[0003] Metal deep drawing is to use stamping, pull ring or metal mold technology to deform plate metal materials into cylindrical or box-shaped parts. The metal deep drawing process has high productivity and high material utilization, with certain dimensional accuracy and low surface roughness. At the same time, it can manufacture thin-walled and complex parts that are not easy to form by other processing methods. With the increasingly fierce price competition, in order to reduce the cost of raw materials and processes, the battery shell currently uses the metal deep drawing process, which requires the shell material to have excellent tensile ductility.
[0004] At present, stainless steel materials are widely used in products that require deep drawing due to their high elongation, can be used for forming complex shapes with fewer defects, and have excellent work hardening capabilities. However, when stainless steel is used for deep drawing, its strength continues to increase due to work hardening, and stress is locally concentrated, resulting in fracture. Summary of the invention
[0005] The purpose of the present invention is to overcome the disadvantage of the prior art that steel is used as the material of a battery housing and is prone to breakage during deep drawing processing, and to provide a battery housing, a battery including the housing and an electrical device thereof.
[0006] To achieve the above object, in a first aspect of the present invention, the present invention provides a battery casing, wherein the material of the casing comprises steel, and the components of the steel comprise Ti, Nb and Cr, wherein the mass percentage of Cr is ≥16wt.% based on the total mass of the steel;
[0007] The housing includes an end wall;
[0008] The housing satisfies the following relationship: ;
[0009] Wherein, h is the height of the shell, in mm;
[0010] d is the thickness of the end wall, in mm;
[0011] b is the mass percentage of Ti based on the total mass of steel, in wt.%;
[0012] c is the mass percentage of Nb based on the total mass of steel, in wt.%.
[0013] As a preferred embodiment of the present invention, the housing satisfies the following relationship: .
[0014] As a preferred embodiment of the present invention, the range of h is 20-300 mm.
[0015] As a preferred embodiment of the present invention, the range of h is 50-270 mm.
[0016] As a preferred embodiment of the present invention, the range of d is 0.2-1.5 mm.
[0017] As a preferred embodiment of the present invention, the range of d is 0.5-1.0 mm.
[0018] As a preferred embodiment of the present invention, the range of b+c is 0.2-0.8 wt.%.
[0019] As a preferred embodiment of the present invention, the range of b+c is 0.25-0.5 wt.%.
[0020] As a preferred embodiment of the present invention, the range of b is 0.05-0.2 wt.%.
[0021] As a preferred embodiment of the present invention, the range of c is 0.17-0.5 wt.%.
[0022] As a preferred embodiment of the present invention, the housing further includes a side wall, and the housing also satisfies the following relationship: , where f is the thickness of the shell side wall, in mm.
[0023] As a preferred embodiment of the present invention, the range of f is 0.1-1.2 mm.
[0024] As a preferred embodiment of the present invention, the range of d is 0.3-1.2 mm.
[0025] As a preferred embodiment of the present invention, a pressure relief structure is provided on an end wall at one end of the shell.
[0026] As a preferred embodiment of the present invention, the pressure relief structure includes a weak portion, and the shell also satisfies the following relationship: , where m is the residual thickness of the weak part, in mm.
[0027] As a preferred embodiment of the present invention, the range of m is 0.01-0.5 mm.
[0028] As a preferred embodiment of the present invention, an end cover is provided on the other end of the shell relative to the end wall, the end cover is fixedly connected to the side wall, and a through hole for arranging a pole assembly is provided on the end wall or the end cover.
[0029] As a preferred embodiment of the present invention, the through hole is provided on the end wall, and the shell also satisfies the following relationship: , where k is the ratio of the area of the through hole to the area of the end wall where the through hole is located.
[0030] As a preferred embodiment of the present invention, the range of k is 0.00125-0.1.
[0031] As a preferred embodiment of the present invention, a liquid injection hole is provided on the end wall, and the shell also satisfies the following relationship: , wherein z is the ratio of the area of the injection hole to the area of the end wall.
[0032] As a preferred embodiment of the present invention, the range of z is 0.001-0.08.
[0033] As a preferred embodiment of the present invention, the steel further comprises C, Si, Mn, P, S and Fe.
[0034] In a second aspect of the present invention, the present invention provides a battery, comprising the battery casing as described above.
[0035] In a third aspect of the present invention, the present invention provides an electrical device comprising the battery as described above.
[0036] The beneficial effects of the present invention are:
[0037] The present invention controls the relationship between the content of Ti and Nb and the shell height and the end wall thickness, so that the steel with the Ti and Nb content can meet the deep drawing processing performance of the battery shell, and the shell after molding has good mechanical properties such as pressure bearing capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a schematic diagram of the overall structure of the battery in Example 1;
[0039] Figure 2 This is a schematic diagram of the overall structure of the battery of Example 1 from another perspective;
[0040] Figure 3This is a schematic structural diagram of the housing of Example 33;
[0041] Figure 4 for Figure 3 A local enlarged view of point A;
[0042] Figure 5 This is a schematic diagram of the structure of the housing of Example 38;
[0043] Figure 6 This is a schematic diagram of the overall structure of the battery of Example 45.
[0044] The illustrations are as follows:
[0045] 1-shell, 11-end wall, 12-end cover, 13-side wall, 2-weak part, 3-through hole, 4-liquid injection hole, 5-pole assembly. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0048] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0049] An embodiment of the present invention provides a battery case, wherein the material of the case 1 includes steel, and the components of the steel include Ti, Nb and Cr, wherein the mass percentage of Cr is ≥16 wt.% based on the total mass of the steel;
[0050] The housing 1 comprises an end wall 11;
[0051] The housing 1 satisfies the following relationship: ;
[0052] Wherein, h is the height of the housing 1, in mm;
[0053] d is the thickness of the end wall 11, in mm;
[0054] b is the mass percentage of Ti based on the total mass of steel, in wt.%;
[0055] c is the mass percentage of Nb based on the total mass of steel, in wt.%.
[0056] The shape of the battery housing 1 is mostly columnar, including cylindrical and prismatic. At the same time, the battery housing 1 provided by the present invention is manufactured by a deep drawing process. During the deep drawing process, an opening surface is required for the punch to enter. The opening surface is generally one of the bottom surfaces of the cylindrical battery, and the other bottom surface is integrally formed with the side wall 13. In the present invention, the end wall 11 is defined as a surface integrally formed with the side wall 13, and an end cover 12 is provided at the opening surface. The end cover 12 is fixedly connected to the side wall 13, which can be welded, riveted, bonded, etc., which does not affect the implementation of this solution.
[0057] Cr is the main element that determines the corrosion resistance of stainless steel. It can increase the matrix electrode potential, thereby significantly improving the corrosion resistance of steel. In addition, as the main component of the oxide film, Cr helps to form a more stable oxide film and improve the oxidation resistance at high temperatures.
[0058] During the deep drawing process, when the side wall 13 is stretched after the end wall 11 is formed, the end wall 11 is used as the stretching reference, and the end wall thickness d remains basically unchanged. The initial thickness of the side wall 13 is the same as the end wall thickness d, and becomes smaller as it is stretched. Therefore, as the height h of the shell 1 increases, the deep drawing performance required by the shell 1 should be improved accordingly, especially when the end wall thickness d of the shell 1 is relatively thin, but the height h of the shell 1 is relatively high, that is, the initial thickness of the side wall 13 is small but the side wall 13 is stretched relatively high, then the side wall 13 formed during the stretching process will be thinner, and the strength requirement for the shell 1 not to be broken during the stretching process is higher, and the deep drawing performance of the shell 1 needs to be better to avoid hardening of the shell 1 during the deep drawing process, local force concentration, and fracture.
[0059] In the present invention, by controlling the content of titanium (Ti) and niobium (Nb), the deep drawing performance of the steel can be regulated to a certain extent, avoiding stress concentration during deep drawing and causing fracture and increased defect rate. In particular, when the end wall 11 is thin and the drawing height is high, that is, the height of the shell 1 is high, the steel needs to have better deep drawing performance to avoid fracture of the shell 1 during the deep drawing process.
[0060] However, the good deep drawing performance of steel means that the steel is easy to deform, which may make the shell 1 have poor pressure bearing capacity after forming, resulting in reduced safety performance of the battery. In addition, if the deep drawing performance is poor, even if the shell 1 is barely formed, the mechanical properties of the shell 1 after forming are poor, and its safety performance is difficult to guarantee. Therefore, it is necessary to balance the deep drawing performance of the shell 1 during processing and the pressure bearing performance after processing.
[0061] like If the value of is too small, it means Too small, or the content of at least one of Ti and Nb is too high, If the elongation is too small, the elongation will not be enough, while if the Ti content is too high, the recrystallization behavior of the stainless steel may change, thereby affecting the mechanical properties and corrosion resistance of the stainless steel, and further causing the forming rate of the shell 1 to decrease. If the Nb content is too high, the elongation and deep drawing performance of the material will decrease. If the value of is too large, it means Too large, or the content of at least one of Ti and Nb is too low, The larger the value, the greater the degree of stretching required. However, if the content of Ti and Nb is too low, the intergranular corrosion will increase during deep drawing and the formability of the shell 1 will deteriorate. Therefore, Need to be controlled within an appropriate range.
[0062] Therefore, the present invention makes the mass percentage b of Ti, the mass percentage c of Nb, the thickness d of the end wall 11, and the height h of the shell 1 satisfy , so that the deep drawing property of the steel can meet the size of the shell 1 to be processed, avoid breakage during deep drawing processing, improve the processing yield, and also make the formed shell 1 have better mechanical properties to ensure the safety of the battery.
[0063] In some embodiments of the present invention, The specific selection can be 50, 60, 70, 80, 90, 100, 110, 120, 135, 150, 200, 300, 500, 800, 1000, 2000, 3000, 4000, 5000, 6000, 6500, 6800, 6900, 6950, 7000, or it can be an interval range formed by any two of the above values, such as 100-6000, 135-5000, 1000-7000, etc.
[0064] In one embodiment, the housing 1 satisfies the following relationship: .
[0065] In this solution, the shell 1 that satisfies the above relationship can achieve a higher processing yield during deep drawing.
[0066] In one embodiment, the range of h is 20-300 mm.
[0067] In some embodiments of the present invention, the specific selection of h can be 20 mm, 25 mm, 30 mm, 35 mm, 40 mm, 50 mm, 60 mm, 70 mm, 80 mm, 100 mm, 120 mm, 150 mm, 180 mm, 200 mm, 220 mm, 250 mm, 270 mm, 280 mm, 290 mm, 295 mm, 300 mm, or it can be an interval range formed by any two of the above values, such as 50-270 mm, 100-220 mm, 80-300 mm, etc.
[0068] In one embodiment, the range of h is 50-270 mm.
[0069] In one embodiment, the range of d is 0.2-1.5 mm.
[0070] In some embodiments of the present invention, the specific selection of d can be 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.15 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.45 mm, 1.5 mm, or it can be an interval range formed by any two of the above values, such as 0.4-1.0 mm, 0.5-1.2 mm, 0.2-0.8 mm, etc.
[0071] In one embodiment, the range of d is 0.5-1.0 mm.
[0072] In one embodiment, the range of b+c is 0.2-0.8 wt.%.
[0073] In some embodiments of the present invention, the specific selection of b+c can be 0.2 wt.%, 0.25 wt.%, 0.3 wt.%, 0.35 wt.%, 0.4 wt.%, 0.45 wt.%, 0.5 wt.%, 0.55 wt.%, 0.6 wt.%, 0.65 wt.%, 0.7 wt.%, 0.75 wt.%, 0.8 wt.%, or it can be an interval range formed by any two of the above values, such as 0.2-0.5wt.%, 0.3-0.8 wt.%, 0.25-0.5 wt.%, etc.
[0074] In one embodiment, the range of b+c is 0.25-0.5 wt.%.
[0075] Ti and Nb are both carbon and nitrogen stabilizing elements, which can combine with carbon and nitrogen to form NbC, NbN, TiC, and TiN, thus improving the strength of steel. At the same time, the precipitation of Ti carbides can significantly improve the plasticity and impact toughness of steel, ensure that the steel has good deep drawing forming properties, and inhibit the formation of chromium carbon and nitrogen oxides in steel, thereby improving the intergranular corrosion resistance of stainless steel. Trace amounts of Nb can improve the strength of steel without affecting the plasticity or toughness of steel. Nb carbides and oxides can improve the impact toughness of steel and reduce its brittle transition temperature due to the effect of grain refinement.
[0076] In one embodiment, the range of b is 0.05-0.2 wt.%.
[0077] Excessive Nb will lead to the formation of coarse Fe2Nb hard phase, reducing the elongation and deep drawing properties of the material, and too much NbN will also reduce the hot plasticity of the steel, so the Nb content is controlled within a certain range.
[0078] In some embodiments of the present invention, the specific selection of b can be 0.05 wt.%, 0.07 wt.%, 0.1wt.%, 0.12 wt.%, 0.15 wt.%, 0.17 wt.%, 0.2 wt.%, or it can be an interval range formed by any two of the above values, such as 0.05-0.15 wt.%, 0.07-0.17 wt.%, 0.1-0.2 wt.%, etc.
[0079] In one embodiment, the range of c is 0.17-0.5 wt.%.
[0080] When the Ti content is high, the number of TiN inclusions is large and the size is large, which affects the surface quality of the steel. Therefore, the Ti content needs to be controlled within a certain range.
[0081] In some embodiments of the present invention, the specific selection of c can be 0.17 wt.%, 0.2 wt.%, 0.22 wt.%, 0.25 wt.%, 0.27 wt.%, 0.3 wt.%, 0.35 wt.%, 0.4 wt.%, 0.45 wt.%, 0.5 wt.%, or it can be an interval range formed by any two of the above values, such as 0.25-0.5 wt.%, 0.17-0.35 wt.%, 0.2-0.4wt.%, etc.
[0082] The test method of Ti, Nb and Cr content is not limited, and those skilled in the art can test Ti, Nb and Cr content according to conventional methods, such as inductively coupled plasma method, X-ray fluorescence spectrometry, etc.
[0083] Inductively coupled plasma method:
[0084] (1) Sample preparation: Stainless steel samples need to be properly pretreated, such as being dissolved in a specific acid solution to release the elements to be tested. For example, aqua regia is used to dissolve the sample, or a specific mixed acid system is used for digestion to ensure the effective release of the elements.
[0085] (2) Analysis method: The analysis methods of ICP-OES mainly include the standard curve method and the internal standard method. The standard curve method draws a relationship curve between the concentration of the standard solution and the emission intensity at the corresponding wavelength, and compares the emission intensity of the sample solution with the standard curve to obtain the content of each element in the sample. The internal standard method selects an element with similar chemical properties to the element to be measured and a constant content in the sample as an internal standard. By comparing the emission intensity ratio of the element to be measured and the internal standard element, the influence of factors such as sample composition and experimental conditions is eliminated.
[0086] X-ray fluorescence spectrometry
[0087] (1) Sample preparation: First, the stainless steel sample needs to be properly processed to facilitate X-ray penetration and stimulate fluorescence. This may include cutting, grinding, polishing and other steps to ensure that the sample surface is flat and free of contamination.
[0088] (2) X-ray excitation: High-energy X-rays are used to irradiate the sample surface to stimulate the characteristic X-ray fluorescence of each element. The wavelength or energy characteristics of these fluorescence spectra correspond to the type of element, so it is possible to determine which elements are contained in the sample.
[0089] (3) Spectrum collection and analysis: The X-rays reflected from the sample surface and the fluorescence spectrum emitted are collected by a spectrometer. The type and content of the element can be determined by the position and intensity of the characteristic spectral lines.
[0090] (4) Matrix effect correction: Due to the interaction between various elements in stainless steel (matrix effect), the collected spectral data needs to be corrected to eliminate the influence of this interaction on the analysis results and improve the accuracy of the analysis.
[0091] (5) Interpretation of results: Based on the corrected data, the content of each element in the stainless steel can be calculated, and then its performance and quality can be evaluated.
[0092] In one embodiment, the housing 1 further includes a side wall 13, and the housing 1 also satisfies the following relationship: , wherein f is the thickness of the side wall 13 of the shell 1, and its unit is mm.
[0093] Since the end wall 11 and the side wall 13 are formed in one piece by deep drawing, the greater the height of the shell 1, that is, the greater the drawing ratio of the side wall 13, the higher the deep drawing performance requirements of the steel, especially the change in the thickness of the end wall 11 during the deep drawing process is smaller than the change in the thickness of the side wall 13, that is, in the same shell 1, the thickness of the side wall 13 will not exceed the thickness of the end wall 11. If the thickness of the end wall 11 is larger but the thickness of the side wall 13 is smaller, it means that the material drawing ratio of the side wall 13 is larger and it is difficult to form in one piece.
[0094] In some embodiments of the present invention, the The options can be 0.5, 0.6, 0.8, 1, 2, 3, 4, 4.5, 5, or an interval range formed by any two of the above values, such as 0.5-2, 0.5-4.5, 1-5, etc.
[0095] In one embodiment, the range of f is 0.1-1.2 mm.
[0096] In some embodiments of the present invention, the specific selection of f can be 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.15, 1.2 mm, or it can be an interval range formed by any two of the above values, such as 0.2-0.8 mm, 0.5-1.0 mm, 0.2-0.5 mm, etc.
[0097] In one embodiment, the range of d is 0.3-1.2 mm.
[0098] In some embodiments of the present invention, the specific selection of d can be 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, or it can be an interval range formed by any two of the above values, such as 0.3-1.0 mm, 0.5-1.0 mm, 0.4-0.8 mm, etc.
[0099] In one embodiment, a pressure relief structure is provided on the end wall 11 at one end of the housing 1 .
[0100] The pressure relief structure on the battery cell plays an important role in the safety of the battery cell. For example, when a short circuit or overcharge occurs, thermal runaway may occur inside the battery cell, resulting in a sudden increase in pressure or temperature. In this case, the internal pressure and temperature can be released outward through the pressure relief structure to prevent the battery cell from exploding or catching fire. The specific form of the pressure relief structure is not limited. It is mainly used to relieve pressure in time when the battery has thermal runaway. Its structure can be a separate explosion-proof plate, with a hole opened on the shell 1 and the explosion-proof plate connected to the hole, or the explosion-proof structure can be formed directly on the shell 1 by stamping or etching.
[0101] In one embodiment, the pressure relief structure includes a weak portion 2, and the housing 1 also satisfies the following relationship: , where m is the residual thickness of the weak portion 2, in mm.
[0102] When the pressure relief structure is relieving pressure, when the preset pressure is reached, the weak part 2 on the explosion-proof plate will explode to achieve pressure relief, thereby ensuring the safety of the battery. The weak part 2 can be a thinned part formed by stamping or laser etching on the explosion-proof plate. The residual thickness of the thinned part is the remaining thickness of the explosion-proof plate after thinning by stamping or laser etching. The residual thickness direction of the thinned part is parallel to the thickness direction of the end wall 11, and the residual thickness of the thinned part is less than the thickness of the end wall 11. The shape of the weak part 2 can be set in the same shape as the explosion-proof plate, that is, a circle of punched out annular thinned parts is set along the edge of the explosion-proof plate as the thinned part. In this way, the weak part 2 is set with a large area and is easier to explode; the thinned part can also be an incomplete circle, but at least one place that is not thinned is retained on the annular thinned part, so that after the pressure is relieved, the explosion-proof plate still has a connection to prevent the explosion-proof plate from flying out as a safety hazard.
[0103] In this solution, the pressure relief structure is directly formed on the shell 1 by stamping or laser etching. Since the pressure relief structure is integrally formed with the shell 1, in order to ensure the processing rate, the strength of the shell 1, and the triggering pressure of the pressure relief structure, the size of the pressure relief structure needs to be compatible with the deep drawing ability of the shell 1. The bursting pressure of the pressure relief structure is related to the strength of the material and the hardness of the weak part 2. In order to avoid mistriggering the pressure relief structure, the residual thickness of the weak part 2 needs to be controlled. Since Ti and Nb are controlled within a specific range, the strength of the steel is improved, and the size of m can be appropriately reduced, so that the weak part 2 can be made thinner, which is convenient for the pressure relief structure to burst when the battery has thermal runaway to protect the battery safety. At the same time, if If the thickness of the weak part 2 is too small, the content of Ti and Nb will be too low, resulting in poor formability. If the thickness of the weak part 2 is too small, the strength of the pressure relief structure will be low, which may cause accidental explosion. If the thickness is too large, the Ti and Nb content will be too high, resulting in a lower molding rate, and the residual thickness m of the weak part 2 will be too large, which is not conducive to the pressure relief structure bursting and releasing heat when the battery has thermal runaway. Need to be controlled within an appropriate range.
[0104] When the end wall 11, the side wall 13, and the weak portion 2 and the through hole 3 on the end wall 11 are integrally formed, it is necessary to consider the processing performance during deep drawing, the strength of the shell 1 after forming, and the bursting pressure of the pressure relief structure. The present invention limits the relationship and range between the residual thickness m of the weak portion 2 and the Ti and Nb content, the ratio z of the area of the injection hole 4 to the area of the end wall 11, and the Ti and Nb content. Under the condition of meeting the deep drawing processing requirements of the height of the shell 1 and the thickness of the end wall, the content of Ti and Nb is further controlled so that when the end wall 11 is deep drawn to form the weak portion 2 and the through hole 3, the performance of the steel can meet the deep drawing process requirements and the shell 1 after forming has sufficient strength.
[0105] In some embodiments of the present invention, the The selection can be 0.004, 0.005, 0.006, 0.008, 0.01, 0.02, 0.04, 0.05, 0.08, 0.1, 0.11, 0.115, 0.12, or it can be an interval range formed by any two of the above values, such as 0.004-0.08, 0.005-0.05, 0.01-0.12, etc.
[0106] In one embodiment, the range of m is 0.01-0.5 mm.
[0107] In some embodiments of the present invention, the specific selection of m can be 0.01 mm, 0.02 mm, 0.03 mm, 0.04 mm, 0.05 mm, 0.06 mm, 0.08 mm, 0.1 mm, 0.12 mm, 0.15 mm, 0.18 mm, 0.20 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, or it can be an interval range formed by any two of the above values, such as 0.1-0.5 mm, 0.01-0.1 mm, 0.2-0.4 mm, etc.
[0108] In one embodiment, an end cover 12 is provided on the other end of the housing 1 relative to the end wall 11 , the end cover 12 is fixedly connected to the side wall 13 , and a through hole 3 for arranging the pole assembly 5 is provided on the end wall 11 or the end cover 12 .
[0109] In one embodiment, the through hole 3 is provided on the end wall 11, and the housing 1 also satisfies the following relationship: , wherein k is the ratio of the area of the through hole 3 to the area of the end wall 11 where the through hole 3 is located.
[0110] The through hole 3 can be provided on the end wall 11 of the housing 1 or on the end cover 12. In the present embodiment, the through hole 3 is provided on the end wall 11. Since the end wall 11 is integrally formed with the housing 1 and the pressure relief structure is also provided on the end wall 11, in order to ensure the processing rate and the strength of the housing 1, the ratio of the area of the through hole 3 to the area of the end wall 11 needs to be adapted to the deep drawing capability of the housing 1. In the present embodiment, the pole assembly 5 is electrically connected to the internal battery cell through the through hole 3. The cross-sectional area of the pole affects the overcurrent. Since the contents of Ti and Nb are controlled within a certain range, the strength of the housing 1 is greater, so that a larger through hole 3 can be provided to accommodate a larger pole assembly 5 and improve the overcurrent. Need to be within a suitable range. If the through hole 3 is too small, the cross-sectional area of the pole is limited, the current carrying capacity is insufficient, the content of Ti and Nb is too high, and the molding rate of the shell 1 is reduced; if If the through hole 3 is too large, the area of the through hole 3 is relatively large and the Ti and Nb contents are relatively low. Since the Ti and Nb contents of the end wall 11 are low, the shell 1 itself is relatively fragile. An excessively large through hole 3 area makes the strength of the end wall 11 even weaker, further increasing the risk of deformation of the shell 1. Therefore, It needs to be set within an appropriate range.
[0111] In some embodiments of the present invention, The specific choice can be 0.005, 0.006, 0.008, 0.01, 0.02, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.42, 0.45, 0.47, 0.5, or it can be an interval range formed by any two of the above values, such as 0.05-0.5, 0.005-0.4, 0.1-0.5, etc.
[0112] In one embodiment, the range of k is 0.00125-0.1.
[0113] In some embodiments of the present invention, the specific selection of k can be 0.00125, 0.0013, 0.0014, 0.0015, 0.0017, 0.002, 0.0025, 0.003, 0.004, 0.005, 0.008, 0.01, 0.02, 0.03, 0.05, 0.07, 0.08, 0.09, 0.095, 0.1, or it can be an interval range formed by any two of the above values, such as 0.00125-0.05, 0.01-0.1, 0.0025-0.1, etc.
[0114] In one embodiment, the end wall 11 is provided with a liquid injection hole 4, and the housing 1 also satisfies the following relationship: , wherein z is the ratio of the area of the injection hole 4 to the area of the end wall 11.
[0115] Since the contents of Ti and Nb are controlled within a certain range, the strength of the shell 1 is increased, and the increase in the area of the injection hole 4 will not cause the overall strength of the end wall 11 to weaken. The content of Ti and Nb is increased, the corrosion resistance is improved, and the strength of the end wall 11 is strengthened. The ratio z of the area of the injection hole 4 and the end wall 11 can be increased, thereby improving the injection efficiency. Need to be within a suitable range. If the content of Ti and Nb is too high, the forming rate of the shell 1 will be low; if the content of Ti and Nb is too high, the area of the injection hole 4 will be too small, which will affect the injection efficiency. If it is too large, the area of the injection hole 4 is too large, causing the end wall 11 to be easily deformed, the content of Ti and Nb is low, and the shell 1 is easily corroded.
[0116] In some embodiments of the present invention, The specific selection can be 0.004, 0.0045, 0.005, 0.007, 0.01, 0.02, 0.04, 0.05, 0.06, 0.08, 0.1, 0.15, 0.2, 0.25, 0.27, 0.28, 0.29, 0.3, or it can be an interval range formed by any two of the above values, such as 0.004-0.05, 0.005-0.1, 0.01-0.03, etc.
[0117] In one embodiment, the range of z is 0.001-0.08.
[0118] In some embodiments of the present invention, the specific selection of z can be 0.001, 0.00125, 0.002, 0.003, 0.0035, 0.004, 0.0045, 0.0047, 0.005, 0.006, 0.007, 0.0075, 0.008, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.075, 0.08, or it can be an interval range formed by any two of the above values, such as 0.00125-0.05, 0.001-0.05, 0.008-0.08, etc.
[0119] The positions of the through hole 3 and the injection hole 4 can be as follows: Figure 3 As shown, the through hole 3 is provided on the end cover 12, and the injection hole 4 is provided on the end wall 11; it can also be as follows Figure 5 As shown, the through hole 3 is provided on the end wall 11, and the injection hole 4 is provided on the end cover 12; the through hole 3 and the injection hole 4 may also be located at the same end of the shell, in which case a hole needs to be opened on the pole assembly as the injection hole. The through hole 3 and the injection hole 4 are respectively provided at both ends of the shell, which is more convenient for battery assembly.
[0120] In one embodiment, the steel further comprises C, Si, Mn, P, S and Fe.
[0121] In some embodiments, the steel includes Fe and the following components in mass percentage: C: greater than 0 and less than or equal to 0.03%, Si: 0~0.75%, Mn: 0~1.0%, P: 0~0.04%, S: 0~0.03%, Cr: 16~30%, Ti: 0.05~0.2%, Nb: 0.17~0.5%, and 0.5% inevitable impurities.
[0122] Method for determining the content of each component:
[0123] The test method of Ti, Nb and Cr content is not limited, and those skilled in the art can test Ti, Nb and Cr content according to conventional methods. For example, inductively coupled plasma method, X-ray fluorescence spectrometry or other test methods do not affect the implementation of this solution.
[0124] Inductively coupled plasma method:
[0125] (1) Sample preparation: Stainless steel samples need to be properly pretreated, such as being dissolved in a specific acid solution to release the elements to be tested. For example, aqua regia is used to dissolve the sample, or a specific mixed acid system is used for digestion to ensure the effective release of the elements.
[0126] (2) Analysis method: The analysis methods of ICP-OES mainly include the standard curve method and the internal standard method. The standard curve method draws a curve between the concentration of the standard solution and the emission intensity at the corresponding wavelength, and compares the emission intensity of the sample solution with the standard curve to obtain the content of each element in the sample. The internal standard method selects an element with similar chemical properties to the element to be measured and with a constant content in the sample as the internal standard. By comparing the emission intensity ratio of the element to be measured and the internal standard element, the influence of factors such as sample composition and experimental conditions is eliminated.
[0127] X-ray fluorescence spectrometry
[0128] (1) Sample preparation: First, the stainless steel sample needs to be properly processed to facilitate X-ray penetration and stimulate fluorescence. This may include cutting, grinding, polishing and other steps to ensure that the sample surface is flat and free of contamination.
[0129] (2) X-ray excitation: High-energy X-rays are used to irradiate the sample surface to stimulate the characteristic X-ray fluorescence of each element. The wavelength or energy characteristics of these fluorescence spectra correspond to the type of element, so it is possible to determine which elements are contained in the sample.
[0130] (3) Spectrum collection and analysis: The X-rays reflected from the sample surface and the fluorescence spectrum emitted are collected by a spectrometer. The type and content of the element can be determined by the position and intensity of the characteristic spectral lines.
[0131] (4) Matrix effect correction: Due to the interaction between various elements in stainless steel (matrix effect), the collected spectral data needs to be corrected to eliminate the influence of this interaction on the analysis results and improve the accuracy of the analysis.
[0132] (5) Interpretation of results: Based on the corrected data, the content of each element in the stainless steel can be calculated, and then its performance and quality can be evaluated.
[0133] In the present invention, there is no particular limitation on the molding method of the shell 1 , and those skilled in the art can perform deep drawing processing on the shell 1 according to conventional technical means.
[0134] Exemplarily, in some embodiments, the preparation process of the battery is as follows:
[0135] 1. Preparation of the shell:
[0136] (1) Preparation of steel: smelting the molten steel to remove impurities, and fine-tuning the molten steel according to the target chemical composition required by the shell 1 to obtain the molten steel with the above-mentioned composition, and then casting it to obtain a steel ingot;
[0137] (2) Preparation of blanks: rolling the steel ingots into coils, and then cutting the coils into plates of appropriate sizes;
[0138] (3) Deep drawing: The sheet is placed in a suitable die and fixed, and then the punch is pressed against the die with a certain force, and the stretching is repeated until the shell 1 is formed.
[0139] (4) Trimming: Remove and trim the excess material during the deep drawing process to ensure that the burrs and flatness of the cut meet the requirements.
[0140] 2. Preparation of positive electrode
[0141] The positive electrode active material, the conductive agent acetylene black and the binder PVDF were mixed in a mass ratio of 96:2:2, and the solvent NMP was added. The mixture was stirred in a vacuum mixer until the system was uniform to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on both surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0142] 3. Preparation of negative electrode sheet
[0143] The negative electrode active material, conductive agent (SP) and binder are mixed in a certain mass ratio (97:1:1), and deionized water is added as a solvent. The mixture is stirred in a vacuum mixer until the system is uniform to obtain the negative electrode slurry. The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain the negative electrode sheet.
[0144] 4. Preparation of electrolyte
[0145] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, FEC is added according to the embodiment and the comparative example, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0146] 5. Preparation of diaphragm
[0147] In this embodiment, a polyethylene film is selected as the separator, and the polyethylene film is cut to form the separator.
[0148] 6. Preparation of lithium-ion batteries
[0149] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode to play an isolating role, and then wound to obtain a bare battery cell;
[0150] The battery cell is placed in the shell 1 (prepared as described above), and the end cover 12 and the shell 1 are connected together by laser welding; after drying, liquid is injected, formed, and constant volume is obtained to obtain a prepared lithium-ion battery.
[0151] The present invention also provides a battery, comprising the battery casing mentioned above.
[0152] The present invention also provides an electrical device, comprising the battery as described above.
[0153] The present invention is further described below with specific embodiments:
[0154] Examples 1-17
[0155] Embodiments 1 to 17 respectively provide a shell 1, wherein the chemical composition of the material of the shell 1 includes: C, Si, Mn, P, S, Ti, Nb, Cr and Fe;
[0156] Taking the total mass of steel as the base, the mass percentages of C, Si, Mn, P and S are: C: 0.03%, Si: 0.7%, Mn: 0.95%, P: 0.04%, S: 0.03% and Cr: 16%.
[0157] The mass percentages of Ti and Nb are shown in Table 1;
[0158] The rest is Fe.
[0159] like Figure 1-Figure 5 As shown in Table 1, the height h of the shell 1 after deep drawing, the thickness d of the end wall 11, the thickness f of the side wall 13 of the shell 1, the residual thickness m of the weak portion 2 after the explosion-proof valve is engraved, the ratio k of the area of the through hole 3 after punching to the area of the end wall 11 where the through hole 3 is located, and the ratio z of the area of the injection hole 4 to the end wall 11 where the injection hole 4 is located are shown in Table 1.
[0160] The battery is prepared as follows:
[0161] 1. Preparation of the shell
[0162] (1) Preparation of steel: smelting the molten steel to remove impurities, and fine-tuning the molten steel according to the target chemical composition required by the shell 1 to obtain the molten steel with the above-mentioned composition, and then casting it to obtain a steel ingot;
[0163] (2) Preparation of blanks: rolling the steel ingot into coils. During the rolling process, the thickness of the coils is adjusted by adjusting the size, gap and rotation speed of the rolling mill rolls to prepare shells 1 with different end wall thicknesses d. The coils are then cut into plates of appropriate sizes.
[0164] (3) Deep drawing: Place the sheet into a suitable die and fix it, then press the punch against the die with a certain force and repeat the drawing until the shell 1 is formed. The area of the end wall 11 of the shell 1 after forming is 1661.06 mm².
[0165] (4) Trimming: Remove and trim the excess material during the deep drawing process to ensure that the burrs and flatness of the cut meet the requirements.
[0166] 2. Preparation of positive electrode
[0167] The positive electrode active material, the conductive agent acetylene black and the binder PVDF were mixed in a mass ratio of 96:2:2, and the solvent NMP was added. The mixture was stirred in a vacuum mixer until the system was uniform to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on both surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0168] 3. Preparation of negative electrode sheet
[0169] The negative electrode active material, conductive agent (SP) and binder are mixed in a certain mass ratio (97:1:1), and deionized water is added as a solvent. The mixture is stirred in a vacuum mixer until the system is uniform to obtain the negative electrode slurry. The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain the negative electrode sheet.
[0170] 4. Preparation of electrolyte
[0171] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, FEC is added according to the embodiment and the comparative example, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0172] 5. Preparation of diaphragm
[0173] In this embodiment, a polyethylene film is selected as the separator, and the polyethylene film is cut to form the separator.
[0174] 6. Preparation of lithium-ion batteries
[0175] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode to play an isolating role, and then wound to obtain a bare battery cell;
[0176] The battery cell is placed in the shell 1 (prepared as described above), and the end cover 12 and the shell 1 are connected together by laser welding; after drying, liquid is injected, formed, and constant volume is obtained to obtain a prepared lithium-ion battery.
[0177] X-ray fluorescence spectrometry
[0178] (1) Sample preparation: First, the stainless steel sample needs to be properly processed to facilitate X-ray penetration and stimulate fluorescence. This may include cutting, grinding, polishing and other steps to ensure that the sample surface is flat and free of contamination.
[0179] (2) X-ray excitation: High-energy X-rays are used to irradiate the sample surface to stimulate the characteristic X-ray fluorescence of each element. The wavelength or energy characteristics of these fluorescence spectra correspond to the type of element, so it is possible to determine which elements are contained in the sample.
[0180] (3) Spectrum collection and analysis: The X-rays reflected from the sample surface and the fluorescence spectrum emitted are collected by a spectrometer. The type and content of the element can be determined by the position and intensity of the characteristic spectral lines.
[0181] (4) Matrix effect correction: Due to the interaction between various elements in stainless steel (matrix effect), the collected spectral data needs to be corrected to eliminate the influence of this interaction on the analysis results and improve the accuracy of the analysis.
[0182] (5) Interpretation of results: Based on the corrected data, the content of each element in the stainless steel can be calculated, and then its performance and quality can be evaluated.
[0183] The measurement methods of d, m and f are as follows:
[0184] The thickness of the end wall 11, the weak portion 2 and the side wall 13 are measured using an ultrasonic thickness gauge. During the measurement, three different positions of the test object are measured and an average value is taken.
[0185] The measurement method of h is as follows:
[0186] The height of the housing 1 is measured using a laser height measuring instrument. During the measurement, three different positions of the test object are measured and the average value is taken.
[0187] Area of through hole 3, injection hole 4 and end wall 11:
[0188] The diameters of the through hole 3, the injection hole 4 and the end wall 11 are measured using a vernier caliper, and the areas of the through hole 3, the injection hole 4 and the end wall 11 are calculated using the area formula of a circle, and finally k and z are calculated.
[0189] Examples 18-26
[0190] Examples 18-26 are similar to Example 1, except that the mass percentages of Ti and Nb are shown in Table 2, and the height h of the shell 1, the thickness d of the end wall 11, and the thickness f of the side wall 13 of the shell 1 after deep drawing are shown in Table 2.
[0191] Examples 27-32
[0192] Examples 27-32 are similar to Example 1, except that the mass percentages of Ti and Nb are shown in Table 3, the height h of the shell 1 after deep drawing, the thickness d of the end wall 11, and the residual thickness m of the weak portion 2 after the explosion-proof valve is engraved and formed are shown in Table 3.
[0193] Examples 33-38
[0194] Examples 33-38 are similar to Example 1, except that Figure 5 As shown, the through hole 3 is provided on the end wall 11, and the injection hole 4 is provided on the end cover 12. The mass percentages of Ti and Nb are shown in Table 4, and the height h of the shell 1 after deep drawing, the thickness d of the end wall 11, and the ratio k of the area of the through hole 3 after punching to the area of the end wall 11 where the through hole 3 is located are shown in Table 4.
[0195] Examples 39-44
[0196] Examples 39-44 are similar to Example 1, except that Figure 3 and Figure 4 As shown, the injection hole 4 is provided on the end wall 11, and the through hole 3 is provided on the end cover 12. The mass percentages of Ti and Nb are shown in Table 5, and the height h of the shell 1 after deep drawing, the thickness d of the end wall 11, and the ratio z of the area of the injection hole 4 to the end wall 11 where the injection hole 4 is located are shown in Table 5.
[0197] Embodiment 45
[0198] Example 45 is similar to Example 1, except that Figure 6 As shown, the shell 1 is a square shell, and the height h of the shell 1 after deep drawing, the thickness d of the end wall 11, the thickness f of the side wall 13 of the shell 1, the residual thickness m of the weak portion 2 after the explosion-proof valve is engraved, the ratio k of the area of the through hole 3 after punching to the area of the end wall 11 where the through hole 3 is located, and the ratio z of the area of the injection hole 4 to the end wall 11 where the injection hole 4 is located are shown in Table 1.
[0199] The square shell is formed as follows:
[0200] (1) Preparation of steel: smelting the molten steel to remove impurities, and fine-tuning the molten steel according to the target chemical composition required by the shell 1 to obtain the molten steel with the above-mentioned composition, and then casting it to obtain a steel ingot;
[0201] (2) Preparation of blanks: rolling the steel ingot into coils. During the rolling process, the thickness of the coils is adjusted by adjusting the size, gap and rotation speed of the rolling mill rolls to prepare shells 1 with different end wall thicknesses d. The coils are then cut into plates of appropriate sizes.
[0202] (3) Deep drawing: Place the sheet into a suitable die and fix it, then press the punch onto the die with a certain force, replace the square die and punch to turn the circle into the square, and repeat the stretching until the shell 1 is formed.
[0203] (4) Trimming: Remove and trim the excess material during the deep drawing process to ensure that the burrs and flatness of the cut meet the requirements.
[0204] Comparative Examples 1-3
[0205] Comparative Examples 1-3 are similar to Example 1, except that the mass percentages of Ti and Nb, the height h of the shell 1 after deep drawing, and the thickness d of the end wall 11 are different, as shown in Table 1 for details.
[0206] Table 1
[0207]
[0208] Table 2
[0209]
[0210] Table 3
[0211]
[0212] Table 4
[0213]
[0214] Table 5
[0215]
[0216] Performance Test:
[0217] The performance test methods of the above comparative examples and embodiments are as follows:
[0218] 1. Shell pressure bearing capacity test:
[0219] (1) Pressure holding test: first seal the injection hole 4 with AB glue or structural glue; then install the shell 1 into the blasting / pressure test tooling, connect the inflation port to the blasting instrument, adjust to the pressure holding mode, and inflate from the shell 1 mouth to the required pressure (such as 3Mpa, 4Mpa, 5Mpa), and maintain for 30s;
[0220] (2) Air tightness test: After the pressure test, the shell 1 is subjected to a helium test. If the leakage rate is ≤1×10-7Pa.m3 / s, the pressure resistance of the shell 1 is qualified under this air pressure.
[0221] 2. The passing rate of deep drawing forming of the shell
[0222] The shell 1 is deep drawn according to the preparation method of the shell 1 described above, and the deep drawing pass rate of 200 shells 1 is statistically prepared.
[0223] It can be seen from Table 1 that in Examples 1-17 and 45, the height h of the shell 1, the thickness d of the end wall, the mass percentage b of Ti, and the mass percentage c of Nb all meet The shell 1 has a stronger pressure bearing capacity than the comparative examples 1-3. At the same time, the local stress is not easy to concentrate and cause fracture during deep drawing. The deep drawing forming pass rate is high and it is more suitable for deep drawing. When the deep drawing forming rate is further improved, especially the shell 1 also meets the requirements of , , When , the deep drawing forming pass rate of the shell 1 is higher.
[0224] As can be seen from Table 2, Examples 18-26 all meet On this basis, considering that the thickness of the side wall 13 of the shell 1 after deep drawing needs to be smaller than the end wall 11, when the thickness of the side wall 13 is much different from that of the end wall 11, that is, the stretching of the side wall 13 is relatively large, the deep drawing performance requirements of the material are higher. From Examples 18-26, it can be seen that When the deep drawing forming pass rate of the shell 1 is higher. Further, when the shell 1 also meets When the shell 1 is formed by deep drawing, the passing rate of deep drawing is further improved, and the shell 1 formed by deep drawing has better pressure bearing capacity.
[0225] As can be seen from Table 3, Examples 27-32 all meet When the weak part 2 of the battery pressure relief structure is formed integrally with the battery housing 1 by deep drawing, if , the weak part 2 can be better deep-drawn, and the deep-drawing pass rate of the shell 1 is high. Especially when the shell 1 also meets The shell 1 is more suitable for deep drawing processing, and its deep drawing forming pass rate is further improved, and the shell 1 after deep drawing processing has stronger pressure bearing capacity.
[0226] As can be seen from Table 4, Examples 33-38 all meet When it is necessary to provide a through hole 3 for the pole assembly 5 on the end wall 11 of the housing 1, if the housing 1 also satisfies , so that the shell 1 can have a sufficient deep drawing forming pass rate, and the pressure bearing capacity is not reduced, especially when the shell 1 also meets The deep drawing forming pass rate is further improved, the pressure bearing capacity is stronger, and the housing 1 after forming is safer.
[0227] As can be seen from Table 5, Examples 39-44 all meet When it is necessary to set a liquid injection hole 4 on the end wall 11 of the shell 1, if the shell 1 also meets 0.000225 , so that the shell 1 can have a sufficient deep drawing forming pass rate, and the pressure bearing capacity of the shell 1 after punching is not reduced, especially when the shell 1 also meets When the deep drawing forming pass rate is further improved, the pressure bearing capacity is stronger, and the housing 1 after forming is safer.
[0228] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A battery casing, wherein the casing (1) is made of steel, characterized in that: The components of the steel include Ti, Nb and Cr, wherein, based on the total mass of the steel, the mass percentage of Cr is ≥16 wt.%; The housing (1) comprises a side wall (13) and an end wall (11) formed integrally with the side wall (13); The housing (1) satisfies the following relationship: ; Wherein, h is the height of the housing (1), in mm; d is the thickness of the end wall (11), in mm; b is the mass percentage of Ti based on the total mass of steel, in wt.%; c is the mass percentage of Nb based on the total mass of the steel, in wt.%; The range of h is 20-300 mm, the range of d is 0.2-1.5 mm, the range of b+c is 0.2-0.8 wt.%, and the range of c is 0.17-0.5 wt.%.
2. The battery housing according to claim 1, characterized in that: The housing (1) satisfies the following relationship: 。 3. The battery housing according to claim 1 or 2, characterized in that: The range of h is 50-270 mm.
4. The battery case according to claim 1 or 2, characterized in that: The range of d is 0.5-1.0 mm.
5. The battery casing according to claim 1 or 2, characterized in that: The range of b+c is 0.25-0.5 wt.%.
6. The battery casing according to claim 1 or 2, characterized in that: The range of b is 0.05-0.2 wt.%.
7. The battery casing according to claim 1, characterized in that: The housing (1) also satisfies the following relationship: , wherein f is the thickness of the side wall (13) of the shell (1), and its unit is mm.
8. The battery casing according to claim 7, characterized in that: The range of f is 0.1-1.2 mm.
9. The battery casing according to claim 7, characterized in that: The range of d is 0.3-1.2 mm.
10. The battery housing according to claim 1, characterized in that: A pressure relief structure is provided on the end wall (11) of the shell (1).
11. The battery housing according to claim 10, characterized in that: The pressure relief structure comprises a weak portion (2), and the shell (1) also satisfies the following relationship: , where m is the residual thickness of the weak portion (2), in mm.
12. The battery casing according to claim 11, characterized in that: The range of m is 0.01-0.5 mm.
13. The battery housing according to claim 1 or 10, characterized in that: An end cover (12) is provided on the other end of the housing (1) relative to the end wall (11); the end cover (12) is fixedly connected to the side wall (13); and a through hole (3) for arranging a pole assembly (5) is provided on the end wall (11) or the end cover (12).
14. The battery casing according to claim 13, characterized in that: The through hole (3) is provided on the end wall (11), and the housing (1) also satisfies the following relationship: , wherein k is the ratio of the area of the through hole (3) to the area of the end wall (11) where the through hole (3) is located.
15. The battery casing according to claim 14, characterized in that: The range of k is 0.00125-0.
1.
16. The battery casing according to claim 1, characterized in that: The end wall (11) is provided with a liquid injection hole (4), and the housing (1) also satisfies the following relationship: , wherein z is the ratio of the area of the injection hole (4) to the area of the end wall (11).
17. The battery casing according to claim 16, characterized in that: The range of z is 0.001-0.
08.
18. The battery casing according to claim 1, characterized in that: The steel also includes C, Si, Mn, P, S and Fe.
19. A battery, characterized in that: Comprising a battery casing as described in any one of claims 1-18.
20. An electrical device, characterized in that: Comprising the battery of claim 19.
Citation Information
Patent Citations
Battery shell, battery comprising shell and electric device of battery
CN119581758A
Battery shell, battery comprising shell and electric device of battery
CN119581759A